Lacan in Bosnia: Salecl, R (1994) The spoils of freedom: Psychoanalysis and feminism after the fall of socialism. London: Routledge. ISBN 0-415--07358-8 pbk. 167 pages. - Spurrett, David; Lahner, Duncan (PINS-Psychology in Society, 2026)
The spoils of freedom is the fourth title in the series Opening Out: Feminism for Today, which, according to series editor Teresa Brennan, will "apply the living insights of feminist critical theory in current social and political contexts" (pvi). Salecl's contribution is an attempt to develop an account of ideology drawing on insights from psychoanalysis, especially a Lacanian notion of jouissance (enjoyment), her essential claim being that "there is no politics without fantasy" (p37). This analysis grows out of her attempt to account for various social changes in Eastern Europe, especially former Yugoslavia, and is in turn deployed in an effort to understand those changes. The main areas Salee! considers are, besides ideology, the rise of conservative moral majorities in post-socialist countries, the nature of war, distributive justice and human rights, the notion of normalisation, power, violence and its legitimation, and several issues relating to feminism.